LOS APORTES DE FRANCISCO DE MIRANDA A LA IDENTIDAD INTEGRACIONISTA DE NUESTRAS AMÉRICAS - Rojas Gómez, Miguel (Cultura Latinoamericana, 2021)
This research highlights the importance of Francisco de Miranda as an authentic thinker, creator of a set of conceptual names of a cultural nature and integrationist identity such as Colombia, Our Americas, Hispanic America and South America, some of which already exist as Our America or South America, but with Miranda would reach a new semantic and pragmatic function of the supranational integrationist identity emancipation, previously not conceived, with transcendence and theoretical historical validity until today. Likewise, based on the documentary foundation of Mirandina roots, it is discussed with those researchers who disqualify the Hispano-American construct of Miranda, emphasizing that the Hispano-American concept has a positive connotation, identity in the difference with the Spanish, and in this sense was assumed by those who advocated it during the 19th and 20th centuries in Latin America, and also by certain Spaniards, without denying that there were Hispanic peninsular who interpreted it from the identity of the same.